Strategic Steps for Implementing An Internal Quality Assurance System in Elementary Schools - Aziroh, Khisma Maula Umadatul; Romi Faslah (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2025)
A culture of quality in the education environment, especially in primary schools, is a fundamental factor in improving the quality of learning and school management. One of the efforts to achieve this is through the implementation of the Internal Quality Assurance System (SPMI), which aims to ensure the fulfillment of educational standards on an ongoing basis. This study aims to analyze the strategic steps in building a culture of quality through the implementation of SPMI in primary schools. The literature research method was used to review various relevant literatures related to the concept of quality culture, SPMI policies, and best practices that have been implemented in various basic education institutions. The results show that the implementation of SPMI requires the commitment of all stakeholders, the establishment of a quality assurance team, thorough socialization, and the integration of the PPPEP cycle (Mapping, Planning, Implementation, Evaluation, and Control) in the learning process. In addition, strengthening the quality culture through habituation, teacher training, and active participation of the school community is the key to success. The conclusion of this study underscores the importance of commitment, synergy and innovation in building a quality and competitive education system.